Superior semicircular canal dehiscence: The neglected pathology - Hilda G. Guzman-Perez (Permanyer, 2021)
The superior semicircular canal dehiscence (SSCD) syndrome is a condition in which the lack of bone overlying the superior semicircular canal is associated with auditory and vestibular signs and symptoms. It was first described in 1998 by Minor et al., using computerized tomography (CT). It has been the diagnosis of patients that suffer from vertigo, hearing loss, chronic disequilibrium, nystagmus, tinnitus, autophony, and/or oscillopsia in the absence of other otological affections. The etiology remains unknown, but it has been concluded that it can be congenital, acquired, or a mixed syndrome, as are many other bone dehiscences. SSCD can be symptomatic or asymptomatic, and its motives are still unknown. The representative manifestation is known as Tullio’s phenomenon or Hennebert’s sign. The diagnosis is based on the clinical history and radiological evidence. CT is the most used study in combination with audiological and vestibular test findings. Repair through the transmastoid approach and the middle fossa approach has been used and has had the best symptomatology resolution. The latter procedure is considered the most effective, although comparative outcomes are still deficient.